2018
DOI: 10.1186/s40792-018-0517-1
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening giant esophageal neurofibroma with severe tracheal stenosis: a case report

Abstract: BackgroundBenign esophageal tumors are relatively rare, and a neurofibroma in the esophagus is extremely rare. Dysphagia is the most common clinical manifestation in patients with esophageal neurofibroma, and no cases of giant esophageal neurofibroma with severe tracheal stenosis have been reported.Case presentationA 73-year-old woman presented with shortness of breath, and computed tomography scan exhibited a giant mediastinal tumor causing severe tracheal stenosis. An upper gastrointestinal endoscopy reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Neurofibroma of the esophagus is a rare benign neoplasm usually made up of a combination of neural and connective tissues [ 1 , 4 ]. Reviews of esophageal submucosal tumors (SMTs) have reported a prevalence of about 0.9% [ 1 , 4 , 5 ]. While most cases of visceral organ neurofibromas are associated with genetic disorders such as Von Recklinghausen’s disease, isolated occurrences have been reported [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Neurofibroma of the esophagus is a rare benign neoplasm usually made up of a combination of neural and connective tissues [ 1 , 4 ]. Reviews of esophageal submucosal tumors (SMTs) have reported a prevalence of about 0.9% [ 1 , 4 , 5 ]. While most cases of visceral organ neurofibromas are associated with genetic disorders such as Von Recklinghausen’s disease, isolated occurrences have been reported [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the three types, localized neurofibromas are the most common in the gastrointestinal (GI) tract. In fact, one case of plexiform neurofibroma of the GI tract is reported so far in the literature [ 1 , 7 ]. Solitary esophageal neurofibroma is the most common form of esophageal neurofibroma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations